Enhancing signal‐to‐noise ratio and resolution in low‐field NMR relaxation measurements using post‐acquisition digital filters. (17th December 2018) - Monaretto, Tatiana; Souza, Andre; Moraes, Tiago Bueno; Bertucci‐Neto, Victor; Rondeau‐Mouro, Corinne; Colnago, Luiz Alberto
Abstract: The traditional way to enhance signal‐to‐noise ratio (SNR) of nuclear magnetic resonance (NMR) signals is to increase the number of scans. However, this procedure increases the measuring time that can be prohibitive for some applications. Therefore, we have tested the use of several post‐acquisition digital filters to enhance SNR up to one order of magnitude in time domain NMR (TD‐NMR) relaxation measurements. The procedures were studied using continuous wave free precession (CWFP‐T1 ) signals, acquired with very low flip angles that contain six times more noise than the Carr–Purcell–Meiboom–Gill (CPMG) signal of the same sample and experimental time. Linear (LI) and logarithmic (LO) data compression, low‐pass infinity impulse response (LP), Savitzky–Golay (SG), and wavelet transform (WA) post‐acquisition filters enhanced the SNR of the CWFP‐T1 signals by at least six times. The best filters were LO, SG, and WA that have high enhancement in SNR without significant distortions in the ILT relaxation distribution data. Therefore, it was demonstrated that these post‐acquisition digital filters could be a useful way to denoise CWFP‐T1, as well as CPMG noisy signals, and consequently reducing the experimental time. It was also demonstrated that filtered CWFP‐T1 method has the potential to be a rapid and nondestructive method to measure fat content in beef and certainly in other meat samples. Abstract : Linear (LI) and logarithmic (LO) data compression, low‐pass infinity impulse response (LP), Savitzky–Golay (SG), and wavelet transform (WA) filters have been tested to enhance signal‐to‐noise ratio (SNR) up to one order of magnitude in low‐field relaxation measurements. The best filters were LO, SG, and WA that have high enhancement in SNR without significant distortions in the ILT relaxation distribution data. These filter were applied to T1 and T2 measurements using CWFP and CPMG pulse sequences.